Processos erosivos às margens das rodovias do Distrito Federal: um estudo de caso - Almeida, Paula Emanoela Silva (2024)
Erosion along the margins of district highways poses a critical problem, with the potential to generate severe socio-environmental and economic impacts. Erosion on the edges of these roads compromises road safety, increases maintenance costs, negatively impacts the quality of water resources, and can lead to losses in local biodiversity. Early identification and mapping of these erosions are crucial for the implementation of effective control and mitigation measures.This study aims to analyze the erosive processes occurring on the margins of highways in the Federal District, utilizing the DF-250 highway as a case study. The research investigates the causes of erosion and their impacts along the highway's right-of-way. Additionally, it presents the actions implemented by the managing agency for the recovery of degraded areas, as well as the costs associated with these recovery measures. The research also mapped critical erosion points on other district highways, aiming to understand the extent of the problem and prioritize areas for intervention. The results include the identification of 23 locations exhibiting erosive processes along highway margins. To comprehend the scale of these erosions, erosion registration forms were completed for district highways, enabling the classification of these erosive processes. Understanding the extent of the erosions is essential for assessing the severity of the problem, planning appropriate interventions, and implementing effective control strategies. Finally, after consultations with public agencies, the protocols directed towards the monitoring and control of erosive processes were investigated.